XSS – A Kid’s Play to Exploit Web Applications: Understanding the Impact and Vulnerabilities of Cross-Site Scripting in Web Applications (Journal of Advances and Scholarly Researches in Allied Education, 2016)
With the evolution of Web 2.0, hiked information sharing through social media, and increasing use of the web in business, websites have become an attractive property to attack. Web application attacks are of greater impact than the other quiet applications and software. Since it's hospitable all and has a wider attack surface. Even Attackers only need an internet browser to access them and perform attacks on them. The most reason is that the attack is often reproduced easily and even is often performed employing a browser. If the attack is performed many users are going to be suffering from it. Cross-site scripting (XSS) is that the category of website vulnerabilities during which an attack is caused by a user’s browser to run the malicious script from the attacker.